Lernumgebungen für den naturwissenschaftlichen Sachunterricht in der Grundschule kooperativ gestalten – ein Projekt zur Förderung des kooperativen Lernens von angehenden Grund- und Förderschullehrkräften. Posterpräsentation auf der 27. Jahrestagung „Diversität und soziale Ungleichheit – Herausforderungen an die Integrationsleistung der Grundschule“ der Kommission „Grundschulforschung und Pädagogik der Primarstufe“ (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hoya, Fabian Karl; Löper, Marwin Felix; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule. Posterpräsentation bei der Auftaktveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Löper, Marwin Felix; Blumberg, Eva; Görel, Gamze; Hellmich, Frank; Hoya, Fabian Karl; Kirsch, Alexander; McAnaney, Jessica; Mester, Theresa; Schulze, Jan Roland; Schwab, Susanne

"The Effectiveness of a Collaborative Learning Environment to Foster Pre-service Teachers’ Self-Efficacy Beliefs concerning Inclusive Education". Posterpräsentation auf der Conference "Teacher Efficacy and Inclusive Education" - Löper, Marwin Felix; Hellmich, Frank; Hoya, Fabian Karl; McAnaney, Jessica; Schulze, Jan Roland; Blumberg, Eva; Schwab, Susanne

Pre-service teachers’ training for inclusive science learning in primary school. Poster Presentation. EARLI SIG 15 `Special Educational Needs´. "Inclusive education´: An integrated research framework on disability, diversity and heterogeneity in education" - Hellmich, Frank; Löper, Marwin Felix; Hoya, Fabian Karl; Blumberg, Eva; Schwab, Susanne

Kooperatives Lernen von Lehramtsstudierenden für den inklusiven Sachunterricht der Grundschule. Posterpräsentation auf der 83. Tagung der Arbeitsgruppe Empirische Pädagogische Forschung (AEPF) - Löper, Marwin Felix; Hoya, Fabian Karl; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Pre-service teachers’ cooperative learning processes and their qualifications for inclusive science learning in primary school. Poster presentation. 6th International Conference on Inclusion - Löper, Marwin Felix; Hoya, Fabian Karl; Hellmich, Frank; Blumberg, Eva; Schwab, Susanne

Die gesellschaftlichen Bedingungen Sozialer Arbeit erforschen - Kuhn, Melanie; Landhäußer, Sandra (Forschungsfelder der Sozialen Arbeit)
Welche Forschungsfelder tun sich in der Sozialen Arbeit auf? Der Band gibt einen systematischen Überblick in die theoretischen Hintergründe und methodischen Zugänge zur Erforschung der gesellschaftlichen Bedingungen, der Organisationen und AdressaLinnen, der professionellen Praxis sowie der Wirkungen der Sozialen Arbeit und illustriert dies an zahlreichen Beispielen aus der Forschungspraxis.

Kritisch-reflexive Praxiserfahrungen in der Grundschule: Das Projekt "Schule für alle" - Pieper, Catania; Kottmann, Brigitte; Miller, Susanne (System. Wandel. Entwicklung. Akteurinnen und Akteure inklusive Prozesse im Spannungsfeld von Institution, Profession und Person)

"Das Beste für mein Kind": Eltern im Übergang zwischen Vorfreude, Sorge und Erwartungsdruck - Grüter, Sandra; Kottmann, Brigitte (Kinder beim Übergang begleiten. Von der Anschlussfähigkeit zur gemeinsamen Verantwortung)

Macht Diagnostik Selektion? - Kottmann, Brigitte; Miller, Susanne; Zimmer, Marianne (Zeitschrift für Grundschulforschung)

The quasi-experimental attitude of teachers: The development of a questionnaire. - Plöger, Wilfried; Scholl, Daniel; Seifert, Andreas (Journal of Education for Teaching)

„Rationale Fischerei“? Das Konzept des Maximum Sustainable Yield im Spannungsfeld von Ökonomie und Ökologie - Sackel, Johanna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

Quantitative Explanation as a Tight Coupling of Data, Model, and Theory - Krüger, Alexander; Tünnermann, Jan; Rohlfing, Katharina; Scharlau, Ingrid (Archives of Data Science, Series A)
What does it mean to explain data patterns? Cognitive psychologists and other scientists face this question when observable phenomena have to be explained in theoretical terms. Frequentist null-hypothesis testing – one prominent approach in psychology – controls error rates. Machine learning – an alternative prominent outside of, but not yet inside psychology – focuses on precise predictions. However, both alternatives often provide little insight into the data. We propose a combination of formal modeling and Bayesian statistical inference to ground explanations in data analysis. We support this approach by reference to philosophy of science and discussions of the current methods crisis in several empirical sciences and illustrate it with an example from visual attention research.

Towards a Computational Model of Child Gesture-Speech Production - Abramov, Olga; Kopp, Stefan; Nemeth, Anne; Kern, Friederike; Mertens, Ulrich; Rohlfing, Katharina (KOGWIS2018: Computational Approaches to Cognitive Science)
Previous work by [1] studied gesture-speech interaction in adults. [1] focussed on temporal and semantic coordination of gesture and speech and found that while adult speech is mostly coordinated (or redundant) with gestures, semantic coordination increases the temporal synchrony. These observations do not necessarily hold for children (in particular with respect to iconic gestures, see [2]), where the speech and gesture systems are still under development. We studied the semantic and temporal coordination of speech and gesture in 4-year old children using a corpus of 40 children producing action descriptions in task oriented dialogues. In particular, we examined what kinds of information are transmitted verbally vs. non-verbally and how they are related. To account for this, we extended the semantic features (SFs) developed in [3] for object descriptions in order to include the semantics of actions. We coded the SFs on the children’s speech and gestures separately using video data. In our presentation, we will focus on the quantitative distribution of SFs across gesture and speech. Our results indicate that speech and gestures of 4-year olds are less integrated than those of the adults, although there is a large variability among the children. We will discuss the results with respect to the cognitive processes (e.g., visual memory, language) underlying children’s abilities at this stage of development. Our work paves the way for the cognitive architecture of speech-gesture interaction in preschoolers which to our knowledge is missing so far.
Keywords: Speech-gesture integration; semantic features

Pädagogisches Wissen von Lehramtsstudierenden im Praxissemester: Ziel schulpraktischen Lernens? - König, Johannes; Darge, Kerstin; Klemenz, Stefan; Seifert, Andreas (Learning to Practice, Learning to Reflect? Ergebnisse aus der Längsschnittstudie LtP zur Nutzung und Wirkung des Praxissemesters in der Lehrerbildung.)

KinU. Kompetenzentwicklung im inklusiven Unterricht. Posterpräsentation bei der Auftaktveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Görel, Gamze; Hoya, Fabian Karl; Löper, Marwin Felix; Albers, Timm; Hellmich, Frank

Does the parental role model behavior play an important role for children’s attitudes towards peers with learning disabilities? Paper presentation. 6th International Conference on Inclusion - Löper, Marwin Felix; Hellmich, Frank

The Role Of Primary School Students’ Perceptions Of Their Parental Behavior For Their Attitudes Towards Peers With Learning Disabilities. Single Paper. ECER 2018 - Löper, Marwin Felix; Hellmich, Frank

Parental Feedback and Primary School Students’ Reading Competencies. Single Paper. ECER 2018 - Hoya, Fabian Karl; Hellmich, Frank

Feedback im Elternhaus und Leseleistungen von Kindern im Grundschulalter. Vortrag auf der 83. Tagung der Arbeitsgruppe Empirische Pädagogische Forschung (AEPF) - Hoya, Fabian Karl; Hellmich, Frank

Bildungshäuser als neue interinstitutionelle Bildungsräume für Kinder und pädagogische Fachkräfte. Ein systemtheoretisches Erklärungsmodell - Bührmann, Thorsten; Büker, Petra (Räume für Bildung – Räume der Bildung. Kongressband zum 25. DGfE-Kongress)

Die Kinderladenbewegung. Ein 'gesellschaftliches Erziehungsexperiment' mit biographischen Auswirkungen als "Neue Soziale Bewegung"? - Bock, Karin; Göddertz, Nina; Heyden, Franziska; Mauritz, Miriam (Soziale Bewegungen und Soziale Arbeit. Von der Kindergartenbewegung zur Homosexuellenbewegung.)
Die Kinderladenbewegung als "Neue soziale Bewegung" steht in engem Zusammenhang mit der Studentenbewegung und der Neuen Frauenbewegung. Das Jahr 1968 markiert damit mindestens symbolisch die Entstehungszeit dieser "Neuen sozialen Bewegungen", deren Verhältnis politisch, sozialgeschichtlich wie gesellschaftstheoretisch nach wie vor unterbelichtet ist. Im Promotionskolleg "Die Kinderladenbewegung", das von 2011 bis 2016 von der Hans-Böckler-Stiftung gefördert wurde, sind wir u.a. der Frage nachgegangen, welche Bedeutung die Kinderläden als "gesellschaftliches Erziehungsexperiment" in den Biographien von Kinderladengründer_innen und Kinderladenkindern hat(te). In unserem Beitrag stellen wir die grundsätzlichen Zugänge vor, die uns für die Frage wichtig erschienen, welche biographischen Auswirkungen und gesellschaftspolitischen Einflüsse die Kinderladenbewegung als institutionelles Erziehungsarrangement hatte. (Orig.).
Keywords: Antiautoritäre Erziehung; Bildungsgeschichte; Frauenbewegung; Kinderladen; Frühpädagogik; Kinderladenbewegung; Studentenbewegung; Achtundsechziger

Antiautoritäre Erziehung in der Kinderladenbewegung. Rekonstruktive Analysen biographischer Entwürfe von Zwei-Generationen-Familien - Göddertz, Nina
Nina Göddertz untersucht die Spuren antiautoritärer Kinderläden in einzelnen Lebensgeschichten sowohl der Eltern- als auch der Kindergeneration. Dabei verknüpft sie sozialgeschichtliche, zeittheoretische, erziehungswissenschaftliche und konzeptionelle Analysen zur Kinderladenbewegung mit der empirischen Rekonstruktion biographischer Entwürfe von Kinderladenfamilien. Ausgangspunkt der Studie ist die Gründung von antiautoritären Kinderläden rund um 1968. In den familialen Generationsanalysen von Kinderladenfamilien identifiziert die Autorin drei verschiedene Muster, die die Verwobenheit von Biographie, Gesellschaft und antiautoritären Erziehungsentwürfen mit dem jeweiligen zeithistorischen Kontext offenlegen.
Keywords: Antiautoritäre Erziehung; soziale Arbeit; Erziehungswissenschaft

Bridging the gap between theory and practice – The effective use of videos to assist the acquisition and application of pedagogical knowledge in pre-service teacher education. - Plöger, Wilfried; Scholl, Daniel; Seifert, Andreas (Studies in Educational Evaluation)

Pedagogical content knowledge of experts and novices – what knowledge do they activate when analyzing science lessons? - Krepf, Matthias; Scholl, Daniel; Plöger, Wilfried; Seifert, Andreas (Journal of Research in Science Teaching)

Professionelle Überzeugungen und motivationale Überzeugungen von Informatiklehrkräften. - Bender, Elena; Schaper, Niclas; Seifert, Andreas (Journal for Educational Research Online)

Health problems of orchestral musicians from a life-span perspective: Results of a large scale study. - Gembris, Heiner; Heye, Andreas; Seifert, Andreas (Music & Science)

Die Veränderung der Selbstwirksamkeitserwartungen und der Berufswahlsicherheit im Praxissemester. Empirische Befunde zur Bedeutung von Lerngelegenheiten und berufsspezifischer Motivation der Lehramtsstudierenden. - Schaper, Niclas; Seifert, Andreas (Learning to Practice, Learning to Reflect? Ergebnisse aus der Längsschnittstudie LtP zur Nutzung und Wirkung des Praxissemesters in der Lehrerbildung.)

Bildungswissenschaftliches Wissen und Kompetenzeinschätzungen von Studierenden im Praxissemester: Veränderungen und Zusammenhänge. - Seifert, Andreas; Schaper, Niclas; König, Johannes (Learning to Practice, Learning to Reflect? Ergebnisse aus der Längsschnittstudie LtP zur Nutzung und Wirkung des Praxissemesters in der Lehrerbildung.)

Die Ordnung der Stadt – Eine vergleichende Untersuchung zur Residenzarchitektur Bückeburgs in der Frühen Neuzeit - Silvestri, Marco (1615 - Recht und Ordnung in Schaumburg)

Kompetenzorientierung – Was angehende Lehrkräfte können und können sollten. - Wapulski, Maik; Seifert, Andreas; König, Johannes (SCHULENRW – Amtsblatt des Ministerium für Schule und Bildung.)

Das geschichtsdidaktische Planungswissen von angehenden Geschichtslehrer/innen – Entwicklung und Pilotierung eines Testinstruments zur Messung des fachdidaktischen Planungswissens von Lehramtsstudierenden im Fach Geschichte. - Wolf, Jörgen; Seiffert, Joanna; Seifert, Andreas; Rothland, Martin; Brauch, Nicola (Geschichte in Wissenschaft und Unterricht)

Can the reduction of an iconic gesture aid long-term learning? A pilot child-robot-study - Mertens, Ulrich J.; Bergmann, Kirsten; Tolksdorf, Nils Frederik; Rohlfing, Katharina J.

Multimodal response behavior of children during word learning with a robot - Tolksdorf, Nils Frederik; Mertens, Ulrich J.; Rohlfing, Katharina J.

Language development from an ecological perspective: Ecologically valid ways to abstract symbols. - Rączaszek-Leonardi,, Joanna; Nomikou, Iris; Rohlfing, Katharina; Deacon, Terrence W. (Ecological Psychology)

Evidence for early comprehension of action verbs. - Nomikou, Iris; Rohlfing, Katharina; Cimiano, Philipp; Mandler, Jean M. (Language Learning and Development)

Evaluation künstlerischen Unterrichts an einer Universität: Einblicke in die Entwicklung von Erhebungsinstrumenten, Prozesse, sowie erste Daten. - Seifert, Andreas; Ahlers, Michael (Jahrestagung der Arbeitsgruppe musikpädagogische Forschung (AMPF))

Learning Culture in Health Care. - Ricken, Britta; Schaper, Niclas; Seifert, Andreas (ISSOTL 2018 Conference (International Society for the Scholarship of Teaching and Learning))

The Role of Informal Learning as a Mediator Between Learning Culture and Work-Related Learning Outcomes. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (JURE Congress)

Personal and Organizational Antecedents of Informal Learning in the Workplace. - Decius, Julian; Schaper, Niclas; Seifert, Andreas (EARLI SIG 14 Conference)

Aspekte bildungswissenschaftlicher Kompetenz. Ansätze, Ergebnisse, Implikationen. - Seifert, Andreas (Arbeitsgruppe der Didaktik der Physik)

Towards a Computational Model of Child Gesture-Speech Production - Abramov, Olga; Kopp, Stefan; Nemeth, Anne; Kern, Friederike; Mertens, Ulrich; Rohlfing, Katharina (KOGWIS2018: Computational Approaches to Cognitive Science)
Previous work by [1] studied gesture-speech interaction in adults. [1] focussed on temporal and semantic coordination of gesture and speech and found that while adult speech is mostly coordinated (or redundant) with gestures, semantic coordination increases the temporal synchrony. These observations do not necessarily hold for children (in particular with respect to iconic gestures, see [2]), where the speech and gesture systems are still under development. We studied the semantic and temporal coordination of speech and gesture in 4-year old children using a corpus of 40 children producing action descriptions in task oriented dialogues. In particular, we examined what kinds of information are transmitted verbally vs. non-verbally and how they are related. To account for this, we extended the semantic features (SFs) developed in [3] for object descriptions in order to include the semantics of actions. We coded the SFs on the children’s speech and gestures separately using video data. In our presentation, we will focus on the quantitative distribution of SFs across gesture and speech. Our results indicate that speech and gestures of 4-year olds are less integrated than those of the adults, although there is a large variability among the children. We will discuss the results with respect to the cognitive processes (e.g., visual memory, language) underlying children’s abilities at this stage of development. Our work paves the way for the cognitive architecture of speech-gesture interaction in preschoolers which to our knowledge is missing so far.
Keywords: Speech-gesture integration; semantic features

Understanding transnational knowledge - Duscha, Annemarie; Klein-Zimmer, Kathrin; Klemm, Matthias; Spiegel, Anna (Transnational Social Review)

Transnational Knowledge (Transnational Social Review)

Expatriate Managers: The Paradoxes of Working and Living Abroad - Spiegel, Anna; Mense-Petermann, Ursula; Bredenkötter, Bastian

Niederländische Maler in Italien. Künstlerreisen und Kunstrezeption im 16. Jahrhundert - Harnack, Maria

Neuer Zugang zur Geschichte - Duschner, Paul (Neue Westfälische)

Wie Handys ins Museum kamen - Duschner, Paul (Neue Westfälische)

Was Museumsbesucher sagen - Duschner, Paul (Neue Westfälische)

Exponate und Ausstellungen in den Augen ihrer Besucher. Vier Beobachtungen aus der Stadtschreiberei Paderborn - Duschner, Paul (Paderborner Historische Mitteilungen)